Metabolic changes in the bone tissue of animals in conditions of experimental cadmium intoxication - Khopta, Nadiia; Ersteniuk, Anna (ScienceRise: Biological Science, 2018)
Objective: to investigate the features of metabolic processes, bioelement composition and mineral density of the bone tissue of white rats (sexually mature males) in conditions of defeat by cadmium ions. Materials and methods. The toxicant (Сadmium chloride, CdCl2, 1,2 mg/kg) was administered to animals for 10 days, and then removed from the experiment on days 1, 14 and 28. The blood and femurs were investigated. Blood levels of calcium-phosphorus metabolism, acidi and alkaline phosphatases, magnesium, Нydroxyproline concentrations were studied by standardized methods using reagent kits, as well as the level of Рarathyroid hormone and Сalcitonin in the development of intoxication. In the ash of the femurs, the content of osteotropic bioelements and toxic cadmium was determined. The bone mineral density (BMD)was investigated using standard x-ray densitometry. Results. An increase in the concentration of total and ionized calcium on the background of increased secretion of Рarathyroid hormone and reduced Сalcitonin has been established; decreased activity of alkaline phosphatase, increased acidi phosphatase, especially on the 14-th day. In animals, an increase in the concentration of Нydroxyproline was observed in the blood (2,5–3,5 times) and a decrease in magnesium. When determining the content of osteotropic bioelements in the ash of the femoral bones of rats under conditions of CdCl2 exposure, a decrease in the content of Сalcium, Мagnesium, Сopper and Zinc in the femoral bones (by 13–45 %) against the background of a significant increase in the content of Cadmium (9,8 times) was found. Also, there is a decrease in BMD, especially low values recorded on the 14th day. Conclusions. The results of complex studies show that under conditions of introduction of CdCl2 into animals, metabolic processes in bone tissue are disturbed, dismicroelementosis develops, the mineral phase of the bone is demineralized, its collagen matrix is destroyed, and resorption dominates over osteosynthesis